MOTIVASI INDONESIA MENANDATANGANI PREFERENTIAL TRADE AGREEMENT DENGAN NEGARA ANGGOTA D-8 TAHUN 2006-2010 - Muhammad Husein; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research will describes about the motivation Indonesia signed a Preferential Trade Agreement (PTA) with Member States D-8 on September 9 2011 which is part of wishes to improve the economy in the export and importThe method used in this paper is qualitative research. Some of the data obtained came from books, journals, articles, newspapers, the internet and other media. In this research also uses the perspective of liberalism, decision-making theory, the theory of economic integration as a supporter of the theory and use the concept of national interest in seeing the cases studied.In this research also describes the factors above signatories Preferential Trade Agreement with member states D-8, which aims to increase the volume of trade export import Indonesia 2006-2010Keywords : Motivation, Preferential Trade Agreement,International Organizations, Export, Import.